THE IDIOMATIC EXPRESSIONS USED BY THE CHARACTERS AS FOUND IN MEGAMIND MOVIE - Bielqis Elfath (Nazharat: Jurnal Kebudayaan, 2021)
The researcher discussed about The Idiomatic Expressions Used by The Characters as Found in Megamind movie. The movie has theme of heroic stories, in the dialogue it is found that the contain of idiomatic expressions, the movie storyline was good, has a good language structure and the movie contain the message that "anyone can be a hero". The purpose of this study is to determine the types of idiomatic expressions, the meaning of idiomatic expressions, and the types of idiomatic expressions that are the most dominant in used by characters such as those found in the Megamind movie. The theory used was Adam Makkai theory to look for types of idiomatic expressions, and the theory of Abdul Chaer to look for the meaning of idiomatic expressions. Characters are people which are represented in a dramatic or narrative work. Idioms are complex expressions whose meaning does not logically follow the individual meanings of their constituents. Idioms are divided into 2 parts, namely idioms of encoding and idioms of decoding. Idioms of decoding are divided into 2, namely sememic idioms and lexemic idioms. Lexemic Idioms are divided into 5 types, namely phrasal verbs idioms, tournure idioms, irreversible binomial idioms, phrasal compound idioms, and incorporating idioms verbs. This research is qualitative research and used descriptive method. Based on the formulation of the problem, this study has revealed three findings. Consists of; First, there are 175 idiomatic types found, contained in 3 character characters in the Megamind movie which are divided into 5 types, namely, phrasal verb idioms found 54 idioms, tournure idioms found 5 idioms, irreversible binomial idioms there is no found idioms that used by each character in Megamind movie, phrasal compound idiom found 93 idioms and incorporating verbs idiom found 23 idioms. Second, there are 9 types of idiomatic meanings used by the characters in the Megamind movie, 3 lexical meanings, 4 contextual meanings, 4 grammatical meanings, 8 conceptual meanings found, 44 associative meanings found, 35 referential meanings found, 2 non-referential meanings were found, 33 denotative meanings, and 42 connotative meanings. Third, the most dominant types of idiomatic expressions used are in the main character in the movie, namely the Megamind character totaling 63 types of Phrasal Compound Idioms and as many as 33 types of Phrasal Verb Idioms.